Developing Entrepreneurial Spirit in Pesantren: Creating Prosperous Educational Institutions - Santosa, Achadi Budi (Perspektif Pendidikan dan Keguruan, 2024)
Some people think that pesantren only focus on spiritual learning, but this is not true, because some pesantren also excel in business education. This study aims to reveal the strategy of Islamic boarding schools in preparing santri to become graduates who have an entrepreneurial spirit. Through a qualitative approach with a case study model, this research seeks to reveal the facts that naturally occur in social settings. Data collection techniques were carried out through interviews, document review and non-participant observation. Data analysis consisted of individual case analysis and cross-case analysis. The results showed that the strategy applied by the manager of the Islamic boarding school was to foster santri to pay more attention to the factors of work spirit, ethics, and loyalty. These actions are carried out through training activities in various forms of business units, providing motivation, providing examples of business management, and providing internship opportunities in the business and industrial world, so that each santri gets hands-on experience in the field.